Medication adherence among elderly - Makhtar, Aniawanis (IIUM Press, International Islamic University Malaysia, 2017)
The demographic aging is a phenomenon observed in many countries of the worldwide. Malaysia has not been spared from demographic transition as experienced worldwide. As a result of this demographic transition, an increasing proportion of the population is at risk of certain chronic health problems. Elderly population, who tend to have more chronic illnesses such as arthritis, diabetes, hypertension and heart disease will require on multiple of medication and have been linked to a greater risk of non-adherence. Medication adherence is important because a lot of studies showed that the patients who were apparently stop taking their medication which can affect to their health outcome and also economy. The objective this study is to determine the prevalence of medication adherence among elderly and factors associated to medication adherence. These factors include socio- demographic, medication factors, knowledge of medication, and belief of medication towards medication adherence. A cross sectional survey design was conducted at the Medical Outpatient Clinic. Convenience sampling method was used to select the respondents. Two hundred elderly patients who came for regular follow up during period December 2009 until February 2010 were selected. Data was analyzed using descriptive and inferential statistic. A logistic regression analysis was performed in order to identify the independent predictors of adherence. In this study, about 57.5% had good medication adherence, 88% had good medication knowledge and 55% had positive medication belief level. In Pearson Chi Square, it was demonstrated that gender (χ2= 4.464, p < 0.05) and knowledge of medication (χ2 = 12.060, p < 0.05) were significantly related to medication adherence. However, in logistic regression analysis, it was found female [Adjusted OR: 2.900; 95% CI (1.567, 5.368)] and knowledge of medication [Adjusted OR: 3.397; 95% CI (1.303, 8.856)] is incorporated predictors of medication adherence among elderly persons. Medication non- adherence is a serious and growing problem among elderly. Elderly can be particularly vulnerable to dangerous medication interactions and other problems related to medication non- adherence. This finding is important for nurses who play an important role in raising elderly population awareness of non-adherence behaviors. Furthermore, nurses are in a unique position to educate patients about the importance in medication adherence.